Food neophobia and its association with food preferences and dietary intake of adults. Issue 5 (3rd November 2019) - Costa, Alexandra; Silva, Cláudia; Oliveira, Andreia
Abstract: Aim: To assess the association of food neophobia (FN) with food preferences, dietary intake and dietary quality. Methods: A cross‐sectional study was conducted in a non‐probabilistic sample of 229 Portuguese adults, aged 18 to 84 years. FN was measured with the FN Scale. Dietary intake over the previous 12 months was assessed by a validated semi‐quantitative food frequency questionnaire. We defined a dietary pattern the Healthy Diet Indicator, to summarise the effects of overall dietary intake. Generalised linear models were performed to test associations in multivariate analyses (controlled for sex, age and education). Results: FN was negatively associated with a general liking for the act of eating ( β ^ = − 2.976, 95 % CI : − 5.324 ; − 0.993 ) and with reduced preferences for specific foods (fruit and vegetables, some types of meat and fish and traditional Portuguese dishes with blood). Those with higher FN showed a lower consumption of fruits and vegetables, but a higher consumption of milk and codfish, a popular Portuguese ingredient. However, FN did not affect the macronutrients and energy intake, as well as sodium, added sugars and fibre intake. Adherence to a healthy dietary pattern was not significantly associated with FN. Conclusions: FN was associated with a decreased consumption and preference for specific foods, but it had no impact on a healthy dietary pattern.